Stump healing in below knee amputations using soft versus rigid dressing (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Different techniques of postsurgical dressings are used after a below-knee amputation (BKA). This study compares the application of soft dressings versus rigid dressings on healing time and hospital stay after BKA.Methods: In this cross sectional prospective analysis of outcome of two types of post-operative dressings after BKA during January 2012 to January 2018 at Shree Bhawani Hospital Birgunj, Nepal. Wound healing time and hospitalisation were compared between soft and rigid dressings.Results: Out of 37 BKA, 20 received soft dressings with knee immobiliser and 17 rigid plaster dressings. Average age of patients in soft dressing group was 41 years (range 10-70) and in plaster dressing group 37.7 years (range 10-70). Two out of 20 (10%) with soft dressing and 13 out of 18 (76.47%) with the rigid dressing healed primarily, p